DNA minor groove recognition of a non-self-complementary AT-rich sequence by a tris-benzimidazole ligand. - Aymami, J (1999)
The crystal structure of the non-self-complementary dodecamer DNA duplex formed by d(CG[5BrC]ATAT-TTGCG) and d(CGCAAATATGCG) has been solved to 2.3 A resolution, together with that of its complex with the tris-benzimidazole minor groove binding ligand TRIBIZ. The inclusion of a bromine atom on one strand in each structure enabled the possibility of disorder to be discounted. The native structure has an exceptional narrow minor groove, of 2.5-2.6 A in the central part of the A/T region, which is increased in width by approximately 0.8 A on drug binding. The ligand molecule binds in the central part of the sequence. The benzimidazole subunits of the ligand participate in six bifurcated hydrogen bonds with A:T base pair edges, three to each DNA strand. The presence of a pair of C-H...O hydrogen bonds has been deduced from the close proximity of the pyrrolidine group of the ligand to the TpA step in the sequence.